Production of alternaria Cassiae inoculum - Avila, Zilá Ribeiro de; Mello, Sueli Corrêa Marques de; Ribeiro, Zilda Maria de Araújo; Fontes, Eliana Maria Gouvea (Pesquisa Agropecuaria Brasileira, 2000)
In order to adjust the methodology of inoculum production, an isolate of the fungus Alternaria cassiae, selected as a biological control agent for sicklepod (Senna obtusifolia) was studied under different culture media and mycelial growth conditions. Homemade V-8 juice medium without CaCO3 addition, incubation on 200-250 mL of medium (around 50% of the flask volume) with agitation at 250 rpm during 48 hours, followed by mycelial mass growth in continuous dark were appropriate conditions for a large scale production of inoculum. The sporulation was aided by incubation of the mycelial mass at 25oC. The use of 300 mL of mycelial mass per pan (29.9 by 44.5 by 5.0 cm ) to induce the sporulation provided rapid dryness and ensured the conidium integrity, indicated by higher infectivity of the inoculum.